Applications of Extracellular Vesicles in Abdominal Aortic Aneurysm - Lu, Shan; Wang, Ruihan; Fu, Weiguo; Si, Yi (Frontiers in Cardiovascular Medicine, 2022)
Abdominal aortic aneurysm (AAA) is a localized expansion of the abdominal aorta which can lead to lethal complication as the rupture of aortic wall. Currently there is still neither competent method to predict the impending rupture of aneurysm, nor effective treatment to arrest the progression of small and asymptomatic aneurysms. Accumulating evidence has confirmed the crucial role of extracellular vesicles (EVs) in the pathological course of AAA, acting as important mediators of intercellular communication. Given the advantages of intrinsic targeting properties, lower toxicity and fair stability, EVs show great potential to serve as biomarkers, therapeutic agents and drug delivery carriers. However, EV therapies still face several major challenges before they can be applied clinically, including off-target effect, low accumulation rate and rapid clearance by mononuclear phagocyte system. In this review, we first illustrate the roles of EV in the pathological process of AAA and evaluate its possible clinical applications. We also identify present challenges for EV applications, highlight different strategies of EV engineering and constructions of EV-like nanoparticles, including EV display technology and membrane hybrid technology. These leading-edge techniques have been recently employed in multiple cardiovascular diseases and their promising application in the field of AAA is discussed.